Common health problems and nursing of fire rescue personnel in urban flood disaster rescue (城市洪涝灾害消防救援人员常见健康问题与护理对策) - LIU Meiman (刘美满); WU Shiju (吴世菊); DU Yunfeng (杜云峰); ZHU Wei (朱伟); WU Junling (吴军玲) (Association of Integrative Nursing, 2022)
Objective To summarize and analyze the common health problems and nursing of fire rescue personnel in flood disaster rescue in Zhengzhou City, Henan Province, so as to providing reference for urban flood relief firefighters to carry out medical security. Methods From July 23 to July 30, 2021, visited the reinforcement of Zhengzhou flood relief and fire fighting teams from 6 provinces and cities, established health records, and according to doctors' diagnosis, the international Classification of diseases (ICD-10) was adopted to collate the data, the disease statistical analysis, ranking, cause analysis, and summarized the nursing countermeasures. Results A total of 2310 fire rescue commanders, 349 fire rescue workers with 361 people-time health problems. Primary Health problems were the skin disease, musculoskeletal diseases, respiratory diseases of the digestive system, etc. In the top eight of the diseases were colds, dermatitis, waist and leg pain, trauma, high blood pressure, joint pain, indigestion. Combined the characteristics of urban flood fighting and disaster relief with the occupational characteristics of firefighters, analyzed the causes of diseases, and given targeted nursing measures. Conclusion The distribution, causes and nursing countermeasures of common diseases in urban flood fighting and disaster relief were summarized and analyzed in time, which has reference value for future medical teams to carry out rescue and disaster fighting by fire rescue teams. (目的 总结分析消防救援人员在河南省郑州市洪涝灾害救援中常见健康问题及护理对策, 为城市抗洪救灾消防员遂行卫勤保障提供参考依据。方法 2021年7月23日-7月30日, 通过对6省增援郑州市抗洪救灾消防队伍开展巡诊、建立健康档案, 并依据医疗诊断, 采取国际疾病分类法(ICD-10)整理资料, 对疾病进行统计分析、排序、原因分析, 并总结给予的护理对策。结果 医疗队共巡诊了2310名消防救援指战员, 其中349名消防救援人员存在361人次健康问题, 健康问题主要集中于皮肤疾病、肌肉骨骼疾病、呼吸消化系统疾病等29种, 排在前8位的疾病为上感、皮疹、腰腿痛、外伤、高血压、关节痛、消化不良、足廯; 结合城市抗洪救灾特点及消防员职业特性, 分析疾病原因, 给予针对性护理措施。结论 及时总结分析城市抗洪救灾中消防救援队伍常见病种分布、原因及护理对策, 对今后医疗队遂行消防救援队伍卫勤医疗保障在疾病预测、护理对策等方面具有重要参考价值。)